ON CAUCHY-BUNIAKOWSKI-SCHWARZ’S INEQUALITY FOR REAL NUMBERS - Dragomir, S. S.; Arslanagić, Š. Z.; Milošević, D. M. (Matematichki Bilten, 1994)
A new refinement of the well known Cauchy-Buniakowski-Schwarz’s inequality for real numbers is given.